2004
DOI: 10.1016/j.cognition.2003.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Lesion analysis of the brain areas involved in language comprehension

Abstract: The cortical regions of the brain traditionally associated with the comprehension of language are Wernicke's area and Broca's area. However, recent evidence suggests that other brain regions might also be involved in this complex process. This paper describes the opportunity to evaluate a large number of brain-injured patients to determine which lesioned brain areas might affect language comprehension. Sixty-four chronic left hemisphere stroke patients were evaluated on 11 subtests of the Curtiss-Yamada Compre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

67
671
8
7

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 876 publications
(763 citation statements)
references
References 52 publications
67
671
8
7
Order By: Relevance
“…Previous studies from our laboratory also found that the posterior superior temporal region showed decreased volume that correlated with thought disorder (Shenton et al, 1992) and abnormal fMRI activity in response to visual words that correlated with levels of positive symptoms in schizophrenic subjects (Kubicki et al, 2003). The middle temporal gyrus has been shown in lesion, stimulation, and neuroimaging studies to be the neural substrate for semantic comprehension at the single word level (Indefry & Levelt, 2000;Boatman, 2004;Bates et al, 2003;Dronkers et al, 2004;Hart & Gordon, 1990). For example, in a study of 101 patients with left hemisphere damage, comprehension was most affected by damage to the middle temporal gyrus (Bates et al, 2003; and see also Dronkers et al, 2004).…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Previous studies from our laboratory also found that the posterior superior temporal region showed decreased volume that correlated with thought disorder (Shenton et al, 1992) and abnormal fMRI activity in response to visual words that correlated with levels of positive symptoms in schizophrenic subjects (Kubicki et al, 2003). The middle temporal gyrus has been shown in lesion, stimulation, and neuroimaging studies to be the neural substrate for semantic comprehension at the single word level (Indefry & Levelt, 2000;Boatman, 2004;Bates et al, 2003;Dronkers et al, 2004;Hart & Gordon, 1990). For example, in a study of 101 patients with left hemisphere damage, comprehension was most affected by damage to the middle temporal gyrus (Bates et al, 2003; and see also Dronkers et al, 2004).…”
Section: Discussionmentioning
confidence: 71%
“…Distractive speech, in addition to correlating with abnormal activation in the middle temporal region, correlated with a small region of left inferior prefrontal cortex. This region (~BA 47) is thought to subserve working memory for semantic features and thematic structure, and may be used to re-analyze and repair utterance (Dronkers et al, 2004). Abnormal activity in this region might impair the ability of patients to use thematic structure and context to constrain their utterances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The left middle temporal gyrus (BA37) is believed to be important for word-level comprehension, especially as the ties between the concepts and corresponding lexical representations (Dronkers et al, 2004). Like posterior cingulated gyrus discussed above, for the pinyin-naming task, the hippocampal gyrus is also related to verbal and auditory memory (Milner, 1974).…”
Section: Discussionmentioning
confidence: 99%
“…lesion overlap, lesion difference, lesion proportion, etc.) summarizing lesion-deficit associations, with the purpose of identifying the region(s) critical for the support of a particular function (Cancelliere and Kertesz, 1990;Damasio et al, 1996;Tranel et al, 1997;Barrash et al, 2000;Haaland et al, 2000;Adolphs et al, 2002;Dronkers et al, 2004;Heberlein et al, 2004). The region of maximal lesion overlap/difference is related to the deficit and typically hypothesized to be critical for the normal function.…”
Section: Discussionmentioning
confidence: 99%